Ethnomathematic Exploration In The Art of Malangan Mask Puppetry - Anggraini, Erni; Toyyibah, Rifqoh; Marhayati, Marhayati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Malang Regency's mask art is a typical East Javanese tradition that is rich in cultural and artistic dignity. However, its existence is currently increasingly threatened due to minimal attention from the public and lack of research on mask art. This research aims to explore the material assemblages and relationships in Malang Regency mask art because it can provide new insights into how mathematics can be integrated into local culture. In addition, research contributions help to preserve mask art and increase public awareness of Javanese cultural values and philosophy in wayang masks. The method used in qualitative research is ethnographic type. The key instrument consists of two resource persons consisting of 1 resource person as a studio owner and performer of the art of masked wayang and 1 resource person as a mask craftsman. Data collection techniques through interviews, observations and documents. The discussion stage resulted in an exploration of the concept of sets and relationships that can be found from the characteristics of wayang mask art. Thus, research exploring ethnomathematics concepts in Malang Regency mask art can enrich mathematical knowledge applied in the local cultural context.